Methodology of system analysis of competitive interaction of institutional organisation - Astraukh, Yuri L. (Journal of the Belarusian State University. Economics, 2021)
The article examines the problem of institutional competitive relations from the standpoint of the phenomenological approach. The analysis, presented in the text of the article, reveals the prevailing contradictory ideas about this phenomenon within the framework of the traditions of comparison using the tool of neoinstitutional analysis. The article presents the results of the analysis of the mechanisms of competitive relations in social systems from the standpoint of the methodology of the general theory, which acquire special significance in the context of the fragmentation of knowledge about modern economic processes and the emerging civilisation crisis.